Sadar Lingkungan dengan Edukasi Komposting di Kelurahan Jatimakmur - Ade Reza Haryadi; Budi Supriyatno; Pretty Failasufa Aziza (WINDRADI: Jurnal Pengabdian Masyarakat, 2023)
The Composting Program in Jatimakmur Village was initiated by the Faculty of Administrative Sciences at Krisnadwipayana University (UNKRIS) with the aim of reducing the volume of organic waste generated and educating the community about the benefits of compost. Through a participatory approach, the program involves local residents in the composting process from household waste. This activity includes not only technical training on composting but also an environmental education campaign to raise awareness about the importance of sustainable waste management. Results from the program indicate increased community knowledge about composting, a reduction in the amount of waste sent to landfills, and the use of compost as an organic fertilizer in gardens and household plants. The program hopes to serve as a model for community-based waste management initiatives in other areas, supporting sustainable development efforts and environmental independence in Jatimakmur Village.